Analisis Pengelolaan Cagar Budaya di Museum Fosil Tambaksari Kabupaten Ciamis - Dian Rudiana; Dini Yuliani; Otong Husni Taufiq (International Forum of Researchers and Lecturers, 2025)
This research was conducted at the Tambaksari Fossil Museum, Ciamis Regency. The purpose of this research is to determine the Analysis of Cultural Heritage Management at the Tambaksari Fossil Museum, Ciamis Regency in 2024. The method used in this research is a qualitative descriptive research method. This method includes observation, interviews, and documentation. Data processing techniques in this research are data reduction, data presentation, and drawing conclusions. There are 5 informants. The results of the research show that the Analysis of Cultural Heritage Management at the Tambaksari Fossil Museum, Ciamis Regency in 2024 has not been running optimally. From the results of the observation, several indicators of problems were found related to the Analysis of Cultural Heritage Management at the Tambaksari Fossil Museum, Ciamis Regency in 2024, including limited adequate facilities and infrastructure in museum management, the lack of a management plan due to limited Human Resources (HR), the absence of a clear breakdown of duties and responsibilities in Museum management, and low community participation in Museum activities and management. The efforts made include submitting a budget for facility improvements to the local government, conducting routine fossil maintenance and conservation, identifying more comprehensive human resource needs, proposing to relevant parties to consider additional staff, and striving to increase public awareness of the importance of cultural preservation and the role of museums through good communication with the local community. Based on the results of the study above, it can be concluded that the overall Analysis of Cultural Heritage Management at the Tambaksari Fossil Museum, Ciamis Regency in 2024 has not been running optimally. To optimize the management of Cultural Heritage at the Tambaksari Fossil Museum, more intensive collaboration is needed between museum managers, the local government, and the community.